Influence of moisture absorption on impact strength and failure behavior of Hybrid Jute-Carbon/Epoxy composite - Lenda, T.A.; Mridha, Shahjahan (Trans Tech Publications Ltd., Switzerland, 2011)
Hybrid jute-carbon/ epoxy composites, fabricated by hand lay-up method with fiber volume fractions of 0.47, 0.58 and 0.68 were used to investigate water absorption behavior as a function of immersion time and fiber content. The effect of moisture content on impact strength and failure modes was also studied. Results show that the moisture absorption increased with increasing the immersion time in waterand it was more with higher fiber fraction specimens. Maximum moisture contents of 0.45%, 0.52% and 0.61% were recorded for the specimens containing fiber volume fractions of 0.47, 0.58 and 0.68, respectively. The impact strength reduced with increasing moisture absorption in all specimens containing different fiber fractions. Composites with higher fiber content gave reduced impact strength under all test conditions. Composites of different fiber fractions and of highest moisture content produced impact strengths about 20 to 28% less than those strengths obtained without water immersion. The 47 vol% fiber specimen was least affected by water immersion and impact strength reduction was only 17% after immersion till saturation. Failure occurred by mainly by delamination and it was evident in all fractured specimens. Results of the effect of impact energy on moisture content have been evaluated using ANOVA ANALYSIS and the results gave errors of 1%, 0.6 % and 0.8 % for 0.47, 0.58 and 0.68 fiber volume fraction specimens, respectively.